2022
DOI: 10.1016/j.envres.2021.112131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of known and unknown confounders on the relationship between air pollution and Covid-19 mortality in Italy: A sensitivity analysis of an ecological study based on the E-value

Abstract: Back in December 2019, the novel coronavirus disease 2019 (Covid-19) started rapidly spreading worldwide, especially in Italy that was among the most affected countries. The geographical distribution of air pollution and Covid-19 mortality in Italy suggested atmospheric pollution as a worsening factor of severe Covid-19 health outcomes. The present nationwide ecological study focused on all 107 Italian territorial areas, aiming to assess the potential association between Particulate Matter concentration, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…They showed that higher levels of long-term ambient fine particulate matter (PM2.5) air pollution were associated with increased excess mortality during the early period of the COVID-19 pandemic. Other researchers have since corroborated this association in Italy ( Aloisi et al, 2022 ; De Angelis et al, 2021 ; Ye et al, 2021 ) and other parts of the world ( Bourdrel et al, 2021 ; Katoto et al, 2021 ; Kogevinas et al, 2021 ; Tchicaya et al, 2021 ). However, exposure to ambient PM2.5 does not occur in isolation from other co-occurring air pollutants.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…They showed that higher levels of long-term ambient fine particulate matter (PM2.5) air pollution were associated with increased excess mortality during the early period of the COVID-19 pandemic. Other researchers have since corroborated this association in Italy ( Aloisi et al, 2022 ; De Angelis et al, 2021 ; Ye et al, 2021 ) and other parts of the world ( Bourdrel et al, 2021 ; Katoto et al, 2021 ; Kogevinas et al, 2021 ; Tchicaya et al, 2021 ). However, exposure to ambient PM2.5 does not occur in isolation from other co-occurring air pollutants.…”
Section: Introductionmentioning
confidence: 73%
“…Notably, the data showed that PM2.5 effects varied significantly by exposure profile clusters, with strong positive associations between PM2.5 and COVID-19 deaths in clusters with higher-income economies of Western Europe and North America (including Italy). A nationwide mortality study in Italy in 2020 found that omitting ambient temperature from multivariable negative binomial regression models resulted in a downward (attenuation) bias of the PM2.5 effect estimate on mortality in the first year of the pandemic ( Aloisi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the epidemiology of COVID-19 is still developing, there is substantial evidence linking the pathological characteristics of COVID-19 critical illness and the causes of death in COVID-19 patients with the conditions caused and/or exacerbated by long-term exposure to air pollutants like NO 2 and PMs. The hypothesis of a COVID-19 air pollution link has been supported by a fast-growing body of literature reporting evidence of positive association between outdoor air pollution and COVID-19 morbidity and mortality in different parts of the world 18 . It is reasonable to suggest that since chronic air pollution has a negative impact on the cardiovascular and respiratory systems, and immune function, it increases the risk of mortality, exacerbates COVID-19 infection symptoms and worsens COVID-19 patients' prognosis 19 – 21 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, most of the studies assessing the effects of exposure to air pollution have applied an ecological study design; i.e., the air pollution estimates were averaged over the same level of spatial aggregation as the COVID-19 data and these aggregates were compared to the COVID-19 incidence, deaths, and/or case fatality rates. Examples include descriptive analyses based on several correlation indices (such as Pearson and Spearman) between the COVID-19 outcomes and the exposures to different air pollutants in separate cities or countries around the world ( Bashir et al, 2020 ; Daes et al, 2021 ; Fatorini and Regoli, 2020 ; Telo-Leal and Macías-Hernandez, 2021 ; Zorn et al, 2020 ; Zoan et al, 2020 ), regression analyses evaluating the association between air pollution exposures and COVID-19 incidence, severity, and lethality, such as simple linear regression models ( Li et al, 2020 ), multivariate Poisson ( Jiang et al, 2020 ) and negative binomial ( De Angelis et al, 2021 ; Aloisi et al, 2022 ) regression models that account for demographic, socio-economic, and meteorological variables; generalized additive models (GAM) ( Zhu et al, 2020b ) and hierarchical multiple regression models ( Coccia, 2020 ).…”
Section: Introductionmentioning
confidence: 99%